EP.FRI.248 The bezoar, the bowel, and the blockage: A rare case of a spontaneously passed phytobezoar. (28th October 2021) - McGuigan, Conor; Davidson, Sophie; Mark, David
Abstract: Background: Bezoar, from the Persian meaning antidote, denotes a trapped mass in the gastrointestinal system. There are several types, but here we present a case of phytobezoar. A phytobezoar is one which is composed of undigestible plant material. While all bezoars account for less than 4% of intestinal obstruction, most occur within the stomach or small intestine. Phytobezoars causing large bowel obstruction appear to be extremely rare. Case report: We present a case of a phytobezoar causing large bowel obstruction in a 29-year-old man. He presented with a four-day history of abdominal pain and distension with associated vomiting and no bowel opening. An abdominal X-ray demonstrated significant dilatation of transverse colon. Subsequent CT revealed large bowel obstruction with transition point in the distal sigmoid. An intraluminal lesion, with mottled appearance, containing locules of gas – a phytobezoar – was noted as the cause. The Patient was clinically well with no peritonism and planned for a flexible sigmoidoscopy in the first instance. However, the patient went on to pass two large, hard bowel motions leading to significant resolution of symptoms. A flexible sigmoidoscopy was carried out to exclude other pathology and demonstrated that the obstruction had been relieved.  Conclusion: While it seems phytobezoar is an incredibly rare cause for large bowel obstruction, most of the literature suggests operative management of the problem by means of laparotomy and enterotomy. This case demonstrates the potential for conservative management and possibility for spontaneous resolution, despite emergency presentation.